Motor play-based learning to enhance cognitive and linguistic development in preschoolers - Ramírez Aguirre , Gardenia Alexandra (2026)
In early childhood education, motor play is a key tool for integral development, although more evidence is required regarding its cognitive and linguistic impact. Therefore, the objective of the study was to analyze the effect of motor play-based learning on the cognitive and linguistic development of preschool children in an urban context. The research, with a quantitative approach and a quasi-experimental pretest-posttest design, applied an intervention program with structured motor play activities to a census sample of children. Data collection was carried out with standardized instruments before and after the intervention, and the data were processed using descriptive and inferential statistics. The results showed favorable variations in cognitive and linguistic development, with consistent changes between measurements. It was concluded that motor play-based learning was linked to improvements in these processes, providing relevant empirical evidence for early childhood education, although the findings are limited to the study's design and sample.